ADAPTASI DAN VALIDASI INSTRUMEN REVISED CYBER BULLYING INVENTORY II (RCBI II) BAGI PESERTA DIDIK SEKOLAH MENEGAH ATAS DI INDONESIA - Theodora Nurmalia; Herdi Herdi; Wirda Hanim (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to adapt and validate the Indonesian version of the Revised Cyber Bullying Inventory II (RCBI II) instrument for high school students in Indonesia. Researchers conducted a confirmatory analysis (CFA) and found out the adaptation scale of Revised Cyber Bullying Inventory II (RCBI II) that can be applied in Indonesia. This study uses a quantitative method of psychometric properties. The research sample was 200 high school students in Indonesia. Data analysis used Confirmatory Factor Analysis (CFA) in the Linear Structural Relationship (Lisrel) program. Based on the Goodness of Fit Statistics, the model fit was obtained with the values: RMSEA: 0.045; ECVI: 1.67; NFIs: 0.87; CFI: 0.94; RFI: 0.83; GFI: 0.91; AGFI: 0.87. The conclusion from the research results is that the Indonesian version of the Revised Cyber Bullying Inventory II (RCBI II) instrument is suitable for use by students in high schools in Indonesia.